Strategic Analysis and Countermeasures of Ecovacs Robotics - Wang, Rui; Jiang, Ying (Transactions on Economics, Business and Management Research, 2023)
With the rapid development of intelligent robots, the market for home cleaning robots, including floor sweeping robots, continues to expand. The floor sweeping robot industry offers a variety of robot products, and as people's living standards improve, the demand for robot products on the market increases, leading to the gradual adoption of floor sweeping robot products by users. However, with the increasing competition in the floor sweeping robot industry and the rapid pace of product updates, Ecovacs Robotics, although a leading company in the industry, still faces a fiercely competitive market environment. This paper focuses on the development of Ecovacs Robotics in the floor sweeping robot industry, analyzing its strategic development based on internal and external resources and capabilities, the Boston Matrix, macro environment, industry environment, global strategy, and competitive strategy. In addition, this study proposes countermeasures for the development of Ecovacs Robotics in response to the current market environment, aiming to facilitate its stable development and advantageous position in the highly competitive floor sweeping robot industry.